PERBEDAAN AWAL WAKTU SHALAT DUNIA: Analisis Aplikasi Athan Tinjauan Terhadap Posisi Matahari dan Letak Geografis - Hasanuddin Muhammad (Al-Maslahah : Jurnal Ilmu Syariah, 2020)
Changes in the position of the sun and the difference in places with old and long nights. There are interesting things to examine changes in the position of the sun and situation, to the differences in the beginning of world prayer time, by analyzing the schedules available at the application athan. This study sampled the methods of the Islamic Sciences of Karachi University, the method of Umm Al Qura Committee, the Egyptian General Authority of Survey method, the method of the Islamic Society of North America each of 3 (three) cities, the method of the World Muslim League 5 (five) total samples 17 city / country and sun position at 8 days. The problem studied is the large number of positions of the sun and the location of different places for the time used for various kinds of information and their use. The results showed that a significant initial number occurred when the sun's position was in the opposite direction (Sun) (June 22) and South backline (December 22), both for the disputed regions in the Northern Hemisphere or in the Southern Hemisphere and the position of the sun was more dominant compared to geographical location